2020
DOI: 10.3233/jad-200483
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Alzheimer’s Disease: A Systematic Review and Meta-Analysis

Abstract: Background: Ambient air pollution has been associated with Alzheimer’s disease (AD) in the elderly. However, its effects on AD have not been meta-analyzed comprehensively. Objective: We conducted a systematic review and meta-analysis to assess the associations between air pollution and AD incidence. Methods: We searched PubMed and Web of Science for indexed publications up to March 2020. Odds risk (OR) and confidence intervals (CI) were estimated for particulate matter (PM)10 (PM10), PM2.5, ozone (O3), nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 63 publications
1
45
0
Order By: Relevance
“…Epidemiological data indicate a strong association between traffic-related air pollution (TRAP) and increased risk of age-related dementia, including Alzheimer’s disease (AD) ( Fu and Yung 2020 ; Peters et al. 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data indicate a strong association between traffic-related air pollution (TRAP) and increased risk of age-related dementia, including Alzheimer’s disease (AD) ( Fu and Yung 2020 ; Peters et al. 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both epidemiologic and animal toxicological studies have begun to address the above limitations, while recent studies have extended that range of PM2.5 exposures included in the epidemiological evidence base (Jung et al, 2015, Qiu et al, 2019). Yet additional studies from more heavily polluted regions are still required (Fu and Yung, 2020).…”
Section: Accepted Articlementioning
confidence: 99%
“…Among them, 5 of 6 showed a positive association between increased exposure to PM2.5 and dementia or AD; 4 of 4 showed an association between NO2 and dementia or AD, while 1 of 3 did so for ozone (O3). Fu and Yung (2020) 5 published a review and meta-analysis of AD and air pollution, and found a 2-fold excess risk of AD for a 10 µg/m 3 increase of PM2.5 among 6 studies, and no increased risk for NO2 in four studies, nor for O3 in three studies. There have been several longitudinal studies since these reviews, with the majority finding positive associations between air pollutants and either dementia or AD [6][7][8][9][10][11][12][13][14] .…”
Section: Mainmentioning
confidence: 99%
“…5. A cohort study conducted in Ontario, Canada by 22 simultaneously accessed the effects of PM2.5, NO2, and O3 on dementia risks, and they also found significant associations with PM2.5 and NO2, but not O3.…”
mentioning
confidence: 99%